As instituições de acolhimento de João Pessoa/ PB segundo a visão das crianças e dos adolescentes acolhidos: avanços e desafios. - Felix, Katarina Vieira Calado (2014)
This investigative study is configured as a Master's Academic Master entitled Institutions Welcoming João Pessoa/PB through the eyes of children and teens received: advances and challenges which aims to analyze the host institutions of the district of Joao Pessoa / PB from the view of children and teens received. It is an investigative outline of a comprehensive research titled "Institutions Welcoming João Pessoa/PB: Progress and Prospects PostNational Plan for the Promotion, Protection and Right of Children to Family and Community", coordinated the Division of Studies and Research in Economic Analysis, Social Policy and Social Work (SEPACOPS), linked to the Federal University of Paraíba. This study analyzes the situation of institutionalized children and adolescents, based on theoretical and legal frameworks such as System Advocacy, permeated by the relevant legislation, and operational documents comprising the Social Protection Network that effective political and social role of offering various specialized services and the juvenile comprehensive care attendances. This investigative process were surveyed ten (10) institutions host of João Pessoa / PB: Home Child Shalom, Mission Restoration House Home Address of Valek, Holiday Homes Manaíra, Home of the Child Jesus of Nazareth, SOS Villages of Paraíba, Home Men of Safe Haven, Safe Haven House for Women, Home and House Passage of Padre Pio of Pietrelcina; addition of 112 (one hundred and twelve) children and adolescents; Ten (10) managers and 103 (one hundred and three) professionals working in these institutions. In methodological terms, conforms as an applied social research of comparative data between the data analyzed from two surveys (2005/2007 and 2012/2013), performed by SEPACOPS. Operationally, this research adopted the System of Evaluation Indicators for Social Policies (SIAPS) of SEPACOPS (2004) using quantitative and qualitative methodologies by adopting four (04) instruments for data collection application with the interview technique. In the process of data analysis, we chose the descriptive statistics for reading discussion of objective data using the SPSS (Statistical Package for Social Sciences) in organizing databases and content analysis for thematic categorization of Bardin (2007). The survey results show that although they acknowledge the advances, especially in terms of legislation on social protection of children and adolescents, the operation of residential care services still have serious weaknesses by not consolidating as an interim protective measure, which is broad challenges to the effectiveness of family and community reintegration. The data analysis confirms the research hypothesis that the Home Service Institutional developed in ten (10) existing institutions in the city of João Pessoa/PB does not become effective in accordance with the National Plan of family and community to expand actions reintegration of children and teens received their families.